Perceived legitimacy of normative expectations motivates compliance with social norms when nobody is watching - Andrighetto, Giulia; Grieco, Daniela; Tummolini, Luca (Frontiers in Psychology, 2015)
Three main motivations can explain compliance with social norms: fear of peer punishment, the desire for others’ esteem and the desire to meet others’ expectations. Though all play a role, only the desire to meet others’ expectations can sustain compliance when neither public nor private monitoring is possible. Theoretical models have shown that such desire can indeed sustain social norms, but empirical evidence is lacking. Moreover it is unclear whether this desire ranges over others’ “empirical” or “normative” expectations. We propose a new experimental design to isolate this motivation and to investigate what expectations people are inclined to meet. Results indicate that, when nobody can assign either material or immaterial sanctions, the perceived legitimacy of others’ normative expectations can motivate a significant number of people to comply with costly social norms.